(untitled) (International Journal of Nursing Education, 2020)
The study was conducted to evaluate the effectiveness of Hand and Foot massage on level of pain perceptionamong Lower Segment Caesarean Section mothers. Quasi experimental non randomized control group designwas adopted for the study. The structured questionnaire was developed to collect the data. The samples wereselected by purposive sampling technique. The study was conducted on 60 lower segment caesarean sectionmothers. The participants were divided into two groups 30 each in study group and control group. Pre testwas done for both the groups by using Numerical Pain Rating Scale. Hand and foot massage was given for30 minutes to the study group for 5 days (Morning). Post test was done for both the study group and controlgroup. The estimated paired ‘t’ value was 1.70 which was significant at p < 0.05. This shows that the handand foot massage is effective in reducing the level of pain perception among Lower Segment CaesareanSection mothers.